Influence of Abutment Screw-Tightening Methods on the Screw Joint: Immediate and Long-Term Stability - Manlin Sun; Yusen Shui; Yuqiang Zhang; Ruiyang Ma; Yuwei Zhao; Hongyu Chen; Ping Yu; Zhi Li; Tingting Wu; Haiyang Yu (International Journal of Dentistry)
Objective. To evaluate the influence of screw-tightening methods on the immediate and long-term stability of dental implant screw joints. Methodology. A total of 150 implants of three different implant systems with different diameters were used in this study. Each group was divided into three subgroups (n = 5), according to the tightening methods (A—tightening with recommended torque and retorque after 10 min; B—tightening with recommended torque, then loosening and immediate retorque; C—tightening with recommended torque only once). The operating time of tightening the assemblies was recorded. Ten minutes later, the immediate removal torque (IRT) (Ncm) was measured. After retightening the assemblies, a dynamic load between 20 and 200 N was applied for 105 cycles, and the postloading removal torque (PRT) (Ncm) was measured. Scanning electron microscopy (SEM) was used to observe the surface topography of the screws. Results. For different types of implants, the IRTs were 11.92 ± 1.04–34.12 ± 0.36 Ncm for method A, 11.64 ± 0.57–33.96 ± 0.29 Ncm for method B, and 10.30 ± 0.41–31.62 ± 0.52 Ncm for method C, and the IRTs of methods A and B were 6.28%–21.58% higher than that of method C (P≤0.046). The PRTs were 4.08 ± 0.77–29.86 ± 0.65 Ncm for method A, 4.04 ± 0.40–29.60 ± 0.36 Ncm for method B, and 2.98 ± 0.26–26.38 ± 0.59 Ncm for method C, and the PRTs of methods A and B were 11.77%–44.87% higher than that of method C (P≤0.016). The removal torque loss rates of methods A (12.49% ± 0.99%–65.88% ± 4.83%) and B (12.84% ± 0.96%–65.35% ± 1.95%) were 3.04%–7.74% lower than that of method C (16.58% ± 0.56%–71.10% ± 1.58%) (P≤0.017). The operating time of method A was much longer than those of methods B and C (P<0.001). The structural integrity disruption of the screw thread was observed according to the SEM results in all postloading groups. Conclusions. Method B (torquing and then loosening and immediate retorquing) increases the screw joint immediate stability by 6.28%–21.58% and the long-term stability by 11.77%–44.87% compared with method C (torquing only once), has comparable screw joint stability compared with method A (retorquing after 10 min), saves time and is recommended in clinical settings.